Acid based disorders in intensive care unit: a hospital-based study - Rajendran, Babu; Mallampati, Seetha Rami Reddy; Jha J., Sheju Jonathan (International Journal of Advances in Medicine, 2019)
Background: Acid base disorders are common in the ICU patients and pose a great burden in the management of the underlying condition. Methods: Identifying the type of acid-base disorders in ICU patients using arterial blood gas analysis This was a retrospective case-controlled comparative study. 46 patients in intensive care unit of a reputed institution and comparing the type of acid-base disorder amongst infectious (10) and non-infectious (36) diseases. Results: Of the study population, 70% had mixed acid base disorders and 30% had simple type of acid base disorders. It was found that sepsis is associated with mixed type of acid-base disorders with most common being metabolic acidosis with respiratory alkalosis. Non-infectious diseases were mostly associated with metabolic alkalosis with respiratory acidosis. Analysis of individual acid base disorders revealed metabolic acidosis as the most common disturbance. Conclusions: These results projected the probability of acid bases disorders in various conditions and help in the efficient management. Mixed acid base disorders are the most common disturbances in the intensive care setup which is metabolic acidosis with respiratory alkalosis in infectious diseases and metabolic acidosis is the most common simple type of acid base disorder.